Linking evidence for targeted blood biomarkers in post-stroke cognitive impairment and dementia - Jinny Hong; Katherine Mun; Katherine Mun; Kyle C. Kern; Kyle C. Kern; Marissa Thirion; Jason D. Hinman; Jason D. Hinman (Frontiers in Stroke)
With improvements in acute stroke treatment and more patients surving the acute stroke period, the identification and prognostication of post-stroke disability is paramount. Post-stroke cognitive impairment and dementia (PSCID) severely impacts the morbidity and mortality of stroke survivors. While clinical factors and imaging are useful in identifying patients at risk for PSCID, blood-based biomarkers are sorely needed to provide cost-effective identification and prognostication for patients at greatest risk. Furthermore, blood-based biomarkers can inform the biologic basis for PSCID and lead to potential treatment targets. This narrative review attempts to summarize currently available research on the use of fluid biomarkers to measure and quantify PSCID using a framework proposed for use in the DISCOVERY Network study of PSCID. In this framework, blood biomarkers are divided into broad pathologic categories including inflammation, neurodegeneration, neuroaxonal injury, and vascular injury. Key biomarkers that have been proposed as relevant to PSCID include interleukin-6, C-reactive protein, β-amyloid 42:40 ratio, neurofilament light chain, and 10 angiogenic molecules. Critical to the assessment of prior studies includes defining the sample collection period and cognitive assessment period of prior studies to assess the temporal pattern of biomarker levels in relation to an incident stroke event. In addition to this comprehensive review, we performed a protein-protein network analysis of the putative blood biomarkers for PSCID and (surprisingly) find they exist in a highly connected protein-protein interaction network centered on inflammatory and neurodegenerative biomarkers suggesting shared biology underlies the pathogenesis of PSCID. Both the literature and this network analysis point to a role for the use of combinatorial blood biomarkers as a methodology to enhance the specificity and sensitivity of putative prognostic biomarkers for PSCID. This review highlights the emerging role for blood biomarkers in evaluating risk for PSCID while also informing the underlying biology that creates synergy between stroke and dementia.